2021
DOI: 10.1371/journal.pone.0254389
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the BioFire FilmArray Blood Culture Identification panel in the adjustment of empiric antimicrobial therapy in the critically ill septic patient

Abstract: Sepsis and septic shock are key contributors to mortality in critically ill patients and thus prompt recognition and management thereof is central to achieving improved patient outcomes. Early initiation of appropriate antimicrobial therapy constitutes a crucial component of the management strategy and thus early identification of the causative pathogen is essential in informing antimicrobial therapeutic choices. The BioFire FilmArray blood culture identification (BCID) panel is a US Food and Drug Administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 25 publications
(41 reference statements)
3
32
0
1
Order By: Relevance
“…The importance of broadening the BioFire FilmArray BCID panel had been highlighted by a study by Ny et al where a subset of bacteraemia cases caused by organisms not detected by the previous version of the test were associated to adverse clinical outcomes and mainly caused by anaerobes [18]. Moreover, despite we did not detect any carbapenem resistant Gram-negatives due to their low prevalence in the Australian setting, the new capability of BCID2 of detecting carbapenemases is going to be extremely relevant in settings with high prevalence of antimicrobial resistance, both for treatment adjustment and for prompt implementation of infection prevention and control practices [19]. With the use of the new version of the test, only 6% (4/62) of pathogens causing bloodstream infections in our study remained unidentified due to isolates not included in the BCID2 panel, while the missed coverage rate with the use of the previous version of the test has been reported as high as 12-30 % [6,8,20,21,22].…”
Section: Discussionmentioning
confidence: 72%
“…The importance of broadening the BioFire FilmArray BCID panel had been highlighted by a study by Ny et al where a subset of bacteraemia cases caused by organisms not detected by the previous version of the test were associated to adverse clinical outcomes and mainly caused by anaerobes [18]. Moreover, despite we did not detect any carbapenem resistant Gram-negatives due to their low prevalence in the Australian setting, the new capability of BCID2 of detecting carbapenemases is going to be extremely relevant in settings with high prevalence of antimicrobial resistance, both for treatment adjustment and for prompt implementation of infection prevention and control practices [19]. With the use of the new version of the test, only 6% (4/62) of pathogens causing bloodstream infections in our study remained unidentified due to isolates not included in the BCID2 panel, while the missed coverage rate with the use of the previous version of the test has been reported as high as 12-30 % [6,8,20,21,22].…”
Section: Discussionmentioning
confidence: 72%
“…Recently, rapid multiplex PCR systems were developed for detecting 18 to 27 pathogens (bacterial, viral, parasitic and fungal) in 75 minutes. These rapid PCR systems have been developed initially for the detection of the main prevalent infectious agents responsible for severe sepsis (FilmArray® BICD kit) 10 and meningoencephalitis ("ME" kit, FilmArray®). 11 , 12 The FilmArray® system is an automated in vitro diagnostic (IVD) device for the detection of bacterial, viral, parasitic or fungal DNA or RNA in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of this sensitivity would be useful in ophthalmology due to the localization of the injured area to be sampled and the ocular pain that makes sampling relatively difficult. Moreover, it has been demonstrated that the use of FilmArray® BCID in patients hospitalized in intensive care for septic shock, allows a modification of the first line antimicrobial treatment towards a treatment targeting the detected pathogen in 32% of patients 13 and to reduce the time of identification of the pathogen by an average of 1.1 day (0.82 days vs. 1.92 days; p < 0.0001) compared to conventional microbiological diagnostic methods. 14 In addition, the use of FilmArray® BCID enabled rapid implementation of additional multidrug-resistant infection prevention and control practices in 14% of patients in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This panel has a sensitivity and specificity for bronchoalveolar and sputum samples of >96%, enabling both the identification of the causative agents of hospital-associated respiratory infections, and also the prevention of the causative agents of secondary infections, including antibiotic-resistant strains of S. aureus and K. pneumoniae [55]. The FilmArray Blood Culture Identification panel detects 33 pathogen and 10 antimicrobial resistance genes associated with bloodstream infections [56]. For patients with sepsis, a leading cause of death in hospital patients, rapid identification of the organism from blood cultures in combination with the indication of pathogen-associated resistance genes is critical for reducing patient morbidity and mortality [57].…”
Section: The Biofire Filmarray Panelsmentioning
confidence: 99%